Homework Help

# equationFind the solutions of x^4 - 3x^2 + 2 = 0

printsaltr | Student, College Freshman | eNoter

Posted May 10, 2011 at 1:56 AM via web

dislike 0 like
equation

Find the solutions of x^4 - 3x^2 + 2 = 0

Tagged with algebra1, discussion

giorgiana1976 | College Teacher | Valedictorian

Posted May 10, 2011 at 9:37 AM (Answer #2)

dislike 0 like

The number of roots of the given equation is 4.

One method to solve it is factorization.

We'll re-write the middle terms as a sum of 2 terms:

-3x^2 = -x^2 - 2x^2

We'll substitute the middle terms by the algebraic sum:

x^4 -x^2 - 2x^2 + 2 = 0

We'll group the first 2 terms and the last 2 terms:

(x^4 -x^2) - (2x^2 - 2) = 0

We'll factorize by x^2 the first group and by 2 the last group;

x^2(x^2 - 1) - 2(x^2 - 1) = 0

We'll factorize by (x^2 - 1):

(x^2 - 1)(x^2 - 2) = 0

We'll set each factor as zero:

x^2 - 1 = 0

We'll re-write the difference of squares, using the formula:

a^2 - b^2 = (a-b)(a+b)

We'll put a = x and b = 1

x^2 - 1 = (x-1)(x+1)

x - 1 = 0

x1 = 1

x + 1 = 0

x2 = -1

We'll do the same with the second factor x^2 - 2:

x^2 - 2 = (x - sqrt2)(x + sqrt2)

x - sqrt2 = 0

x3 = sqrt2

x4 = -sqrt2

The 4 roots of the equation that we've looked for are: {-sqrt2 ; -1 ; 1 ; sqrt2}.

justaguide | College Teacher | (Level 2) Distinguished Educator

Posted May 11, 2011 at 5:02 AM (Answer #3)

dislike 0 like

We have to solve x^4 - 3x^2 + 2 = 0

x^4 - 3x^2 + 2 = 0

=> x^4 - 2x^2 - x^2 + 2 = 0

=> x^2(x^2 - 2) - 1(x^2 - 2) = 0

=> (x^2 - 1)(x^2 - 2) = 0

x^2 = 1

=> x = 1 , x = -1

x^2 = 2

=> x = sqrt 2, x = -sqrt 2

Th solutions of the equation are (-sqrt 2, -1, 1, sqrt 2)

### Join to answer this question

Join a community of thousands of dedicated teachers and students.